Applying Critical Race Theory to Enhance the Racial Inclusivity of Teachers in Canada: A Review of the Literature and Facilitative Programming - Skelton, Lucas (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This review of the literature draws on critical race theory to examine the lack of racial diversity among the teaching force in Canada. Several barriers including systemic racism, non-diverse hiring policies, and arduous certification requirements for immigrant teachers inhibit the racial diversity of the teaching force in several provinces. Manitoba is profiled because one of the province’s leading universities overhauled its Bachelor of Education admissions protocols to admit an increase in BIPOC applicants. Another leading university in the province has implemented policies to increase the number of Indigenous faculty members and pre-service teacher candidates. Understanding the effectiveness of Equity, Diversity, and Inclusion (EDI) policies in Manitoba could result in a more comprehensive understanding of the validity of EDI policies in general. Through a scoping review, this analysis unearthed 34 articles and documents published around the intersection of race, racial diversity, BIPOC educators, and White teachers. This article presents the findings of the literature review by exploring the merits and drawbacks of using critical race theory to elucidate potential barriers and opportunities for affirming linguistic, ethnic, cultural, and racial diversity in the Canadian school system.